The impact of the Grain-for-Green Programme on carbon storage in the Upper Yangtze River Basin based on the PLUS-InVEST model - Minghong Peng; Ye Yang; Yuanjie Deng; Dingdi Jize; Hang Chen; Yifeng Hai; Guojie Liu; Haijun Wang; Tianhui Xie; Hu Li; Ji Luo (Carbon Balance and Management)
Abstract Alterations in land use and land cover (LUCC) play a fundamental role in influencing the variability of ecosystem carbon storage. Evaluating how land use dynamics affect carbon sequestration and projecting future carbon storage scenarios are essential steps toward meeting China’s dual carbon objectives. In this study, we integrated the Patch-generating Land Use Simulation (PLUS) model with the Integrated Valuation of Ecosystem Services and Tradeoffs (InVEST) framework to investigate LUCC dynamics and their implications for carbon storage across the Upper Yangtze River Basin (UYRB) between 2000 and 2020. Furthermore, projections of regional carbon storage were made under multiple Grain-for-Green Programme (GFGP) scenarios extending to the year 2040. Our findings indicated that cultivated land (CL), forest land (FL), and grassland (GL) consistently dominated land use composition within the UYRB, collectively occupying approximately 96.45% of the total area throughout 2000–2020. During this period, construction land (CSL) steadily expanded, primarily at the expense of CL. Both CL and GL experienced substantial reductions. Spatially, carbon storage exhibited a decreasing gradient from east to west, with the Jinsha River Basin exhibiting the greatest levels. Carbon storage values over the two decades were recorded at 6.387 × 10¹⁰ t in 2000, 6.382 × 10¹⁰ t in 2005, 6.379 × 10¹⁰ t in 2010, 6.369 × 10¹⁰ t in 2015, and 6.373 × 10¹⁰ t in 2020. Despite a slight recovery between 2015 and 2020, total carbon storage fell by 0.23% (1.438 × 108 t) overall. This decline was primarily driven by the conversion of high-carbon-density CL and FL into low-carbon-density CSL and GL. Future projections show distinct disparities across four policy scenarios by 2040. Under the Natural Development Scenario (NDS), rapid economic growth and land conversion are projected to result in a carbon storage loss of 1.324 × 108 t. Conversely, the mild, moderate, and strong GFGPS anticipate carbon storage increases of 1.385 × 10⁸ t, 3.157 × 10⁸ t, and 5.136 × 10⁸ t, respectively. The Jialing River Basin shows the highest gains under all GFGPS. Our findings underscore the significance of the GFGP in enhancing regional carbon sequestration, primarily through encouraging afforestation of previously CL and GL and curbing the expansion of CSL. Such insights can guide land-use planning and ecological conservation strategies in the UYRB moving forward.